Effect of a mobile-based, family-centered self-care education program on Health Literacy and Self-Care in Patients with Heart Failure: A Randomized Controlled Trial - Badiyepeymaiejahromi, Zohreh; Khorramkish, Mahsa; Rahmaniankushkaki , Ali Asghar (Investigación y Educación en Enfermería, 2025)
Objective. To evaluate the effect of family-centered self-care education via tele-nursing on health literacy and the self-care status of patients with heart failure. Methods. This study is a randomized, controlled clinical trial. Sixty heart failure patients were randomly allocated into two groups: intervention (n=30) y control (n=30). The researcher conducted six 20-minute sessions on how to take care of yourself in heart failure for active family members of patients in the intervention group via mobile phone on Eitaa APP messenger. Before the intervention and one month after it, patients completed the Heart Failure Health Literacy Questionnaire and the Self-Care Assessment Questionnaire. Results. Inter-group comparisons using the Mann-Whitney test showed that before the intervention, there was no statistically significant difference between the intervention and control groups in terms of mean health literacy scores and self-care behaviors(p<0.05). However, after the intervention, a significant difference emerged, with the intervention group exhibiting higher mean scores than the control group in both questionnaires (p<0.001). Intra-group comparisons further revealed that the intervention group’s mean scores for health literacy and self-care behaviors increased significantly after the intervention compared to before (p<0.001). Conclusion. Family-centered education via mobile phone on Eitaa APP messenger improved both health literacy and self-care status among heart failure patients. Thus, employing tele-nursing to engage the family members of heart failure patients can be an effective strategy for delivering educational interventions as part of the treatment program.